Globalization, poverty, and food security: Summary Paper from the International Conference on Sustainable Food Security For All By 2020 - Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2001)
The author acknowledges that there are sharply divided views on globalization, poverty and food security. He looks at some of the reasons for the disparity of views including differences about the facts and how to interpret them, the meaning of globalization, its main drivers, and its outcomes. Additionally, there are differing views of the link between globalization and poverty. The implications of these disagreements are (1) the need for complementary domestic policies in developing countries to benefit from globalization, and (2) the responsibility of industrialized countries in shaping the operation of the world economy. Diaz-Bonilla outlines important policies both in developing and in industrialized countries and concludes that making globalization work for the poor and hungry requires adequate domestic policies in developing countries and, also, a pro-poor international environment on the part of the industrialized countries, through diplomatic, military, trade, financial, technological, environmental, and institutional policies.